PENGARUH MUTASI DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA DI LINGKUNGAN PT PEGADAIAN (PERSERO) - Sedarmayanti Sedarmayanti; Gun Gun Gunawan (Universitas Kristen Maranatha, 2019)
This study using data analysis methods namely multiple regression models that are used to see the effect of independent variables, namely Mutations (X1) and Organizational Culture (X2) on the dependent variable, namely Job Satisfaction (Y), so that in research this aims to be able to produce data processing that has been done at PT Pegadaian (Persero) Kanwil X Bandung, then tested using the T test and F test, showing that mutation variables and organizational culture simultaneously on job satisfaction shows results as complete as 53.8% or has a Sig. value of 0.000 where this value is smaller than the significance level used is 0.05, which means that H0 is rejected while for partial mutation variables for the variable job satisfaction of 27.04% or having a Sig. value of 0.011 is smaller than 0.05, meaning H0 is rejected so that it only has 1.1% and variables organizational culture on job satisfaction is 51.27% or has a Sig. value of 0.000 smaller than 0.05, which means that H0 is rejected so that it only has an effect of 0% where all of these variables produce a continuum in the good category based on responses from employees as respondents fromfilling the questionnaire. Keywords: Job Satisfaction; Mutations; Organizational Culture